Image of Nursing in the Aftermath of Covid-19 - Dr. Ani Grace kalaimathi,; Dr.V.Hemavathy, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Scientific advancements, numerous novel technology, and an avalanche of medical information have raised the public's demands and expectations for health care. New forms of caring for the sick and the elderly have broadened the concept of medical care.As a result, there is a need to cover health expenses on the one hand, and to improve service delivery and accessibility, as well as medical personnel availability, on the other.Nursing programmes train specialists to care for a variety of patients. The nurse plays an important role in closing health disparities by providing a wide range of treatments across the health-illness spectrum, actively participating in health education and promotion, developing treatment and assessment programmes, participating in multi-professional teams The public's impression of nurses' authority and functions is important components of the nursing profession’s image.These impressions have the potential to influence health-care users, nurses' performance, health policy, and even the decision to become a nurse. The more positive the image of nursing, the more likely students will pick nursing as their future vocation.